Coagulation parameters of captive black-tailed prairie dogs (Cynomys ludovicianus). (January 2016) - Matthews, M.; Eshar, D.
Abstract Black-tailed prairie dogs (Cynomys ludovicianus ) are commonly kept in zoological collections, studied in research, and kept as pets. When presented in states of health and illness, evaluation of selected coagulation parameters can aid in assessment of various coagulopathies, as well as other disease processes such as septicemia, vasculitis, and hepatic disease. This study was conducted in order to determine coagulation parameters in captive black-tailed prairie dogs. Sixteen black-tailed prairie dogs (10 males, 6 females) were presented for annual health evaluations. A blood sample was collected from the jugular vein of each prairie dog while under general isoflurane anesthesia, and prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen and fibrin degradation products (FDP) were evaluated using an automated hemostasis analyzer. Results of these tests showed a median PT of 8.4 s and a median APTT of 23.8 s. Median fibrinogen concentration was 343 mg/dL and median FDPs were less than 5 mcg/mL. Almost no published data exists in regard to coagulation parameters in exotic rodents, and limited data can be found for more common laboratory species. New data presented here can promote better physiological understanding and improve clinical management of this rodent species.